Waves in fluids / Sir James Lighthill. - Lighthill, James, (Sir), 1924- (Cambridge mathematical library, 2001)
Waves in Fluids describes the science of waves in liquids and gases. It provides an analysis of the most important and representative types of waves and how waves interact with flows.